2016
DOI: 10.1017/s0033291716002555
|View full text |Cite
|
Sign up to set email alerts
|

Clinical anxiety promotes excessive response inhibition

Abstract: Background. Laboratory tasks to delineate anxiety disorder features are used to refine classification and inform our understanding of etiological mechanisms. The present study examines laboratory measures of response inhibition, specifically the inhibition of a pre-potent motor response, in clinical anxiety. Data on associations between anxiety and response inhibition remain inconsistent, perhaps because of dissociable effects of clinical anxiety and experimentally manipulated state anxiety. Few studies direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 58 publications
(133 reference statements)
7
32
0
Order By: Relevance
“…Prior work has shown that participants with clinical anxiety showed impaired “go” accuracy overall compared to controls on this, suggesting that there is an overactive adaptive defensive mechanism in clinical anxiety17. Consequently, we suggest that the effect of threat on reaction time observed here could be a reflection of this behavioural inhibition.…”
Section: Discussionsupporting
confidence: 48%
“…Prior work has shown that participants with clinical anxiety showed impaired “go” accuracy overall compared to controls on this, suggesting that there is an overactive adaptive defensive mechanism in clinical anxiety17. Consequently, we suggest that the effect of threat on reaction time observed here could be a reflection of this behavioural inhibition.…”
Section: Discussionsupporting
confidence: 48%
“…On the surface, the fact that attenuation of the startle reflex is only found when viewing pleasant pictures in an anticipatory context seems to support recent studies finding that threat of shock may facilitate response inhibition (e.g., Grillon et al, 2017a, 2017b). In these studies, infrequent NO-GO signals (interspersed among frequent GO signals) showed fewer errors when participants were under threat of shock (i.e., better able to inhibit responses), suggesting that stress facilitates response inhibition, which the researchers note could also be mediated by enhanced sensory processing.…”
Section: Discussionsupporting
confidence: 74%
“…Prior work has linked anxiety-related symptoms to enhanced EF abilities, including better performance monitoring, working memory, and response inhibition. 13,23,30,4850 Thus, increased ability of some EF components may serve to cause or maintain certain clinical symptoms related to fear. Alternatively, at least in a community sample, anxiety or other subthreshold symptoms may improve certain EF functions 51 or task motivation.…”
Section: Discussionmentioning
confidence: 99%
“…18,20,28,29 Notably, some work found links between higher EF ability and anxiety symptomatology in both children and adults. 13,23,30,31 For example, White et al 23 found that enhanced inhibition predicted higher levels of anxiety in children at temperamental risk for anxiety.…”
Section: Introductionmentioning
confidence: 99%